2020
DOI: 10.3390/ijns6040092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Common Internal Standard Material to Reduce Inter-Laboratory Variation and Ensure the Quality, Safety and Efficacy of Expanded Newborn Screening Results When Using Flow Injection Analysis Tandem Mass Spectrometry with Internal Calibration

Abstract: In 2015, the newborn screening (NBS) programmes in England and Wales were expanded to include four additional disorders: Classical Homocystinuria, Isovaleric Acidemia, Glutaric Aciduria Type 1 and Maple Syrup Urine Disease, bringing the total number of analytes quantified to eight: phenylalanine, tyrosine, leucine, methionine, isovalerylcarnitine, glutarylcarnitine, octanoylcarnitine and decanoylcarnitine. Post-implementation, population data monitoring showed that inter-laboratory variation was greater than e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The postoptimization experiments were performed using a simulated sample (protein-precipitated plasma spiked to achieve analyte concentrations approximating the COV), thus negating differences due to sample extraction. Prior to optimization of the method, it was evident that both intra-and interinstrument variability were greater than expected (4). From a practical perspective, the intrainstrument variability at the COV was large enough to potentially result in a false-negative or falsepositive result (e.g., preoptimization, the %RSD is 46% for C5, 24.3% for Leu, and 22.2% for C5DC (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The postoptimization experiments were performed using a simulated sample (protein-precipitated plasma spiked to achieve analyte concentrations approximating the COV), thus negating differences due to sample extraction. Prior to optimization of the method, it was evident that both intra-and interinstrument variability were greater than expected (4). From a practical perspective, the intrainstrument variability at the COV was large enough to potentially result in a false-negative or falsepositive result (e.g., preoptimization, the %RSD is 46% for C5, 24.3% for Leu, and 22.2% for C5DC (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Currently, there are no commercially available, DBS-based external calibrators. Recent studies have demonstrated that inter-laboratory variation can be significantly reduced using a common stable isotope [ 28 ] and by retrospectively harmonizing screening results to a common material [ 29 ].…”
Section: Good (Laboratory) Practice and Reference Materialsmentioning
confidence: 99%
“…A major limitation of the utility of DBS specimens for biomarker analysis is the lack of commercially available, matrix-matched certified reference materials (CRMs) for the various analytes in DBS specimens with which to standardise laboratory tests [ 27 , 28 ]. As a result, DBS calibrators tend to be produced in-house by collecting blood from a healthy donor or using residual pooled patient samples and adding an aqueous enrichment prior to application onto the filter paper.…”
Section: Good (Laboratory) Practice and Reference Materialsmentioning
confidence: 99%